The impact of different urban parks on vegetation structure, microclimate and insect communities - Ishak, Mohamad Ameerul (2019)
The opening of new areas for urban development has led to an increase of threatened habitat of insects due to changes of vegetation and thus introducing climate issues. The urban green spaces such as parks can provide ecosystem services such as microclimate mitigation and enhances the insect biodiversity. However, different types of urban park may have different vegetation structure and microclimatic condition thus may have different influence on the insect communities. Therefore, this study aimed to determine the influence of vegetation structure, microclimate and insect communities at different types of urban park. This study was conducted at three different park types of Taman Rimba Alam (Forest-based Park), Taman Saujana Hijau (Recreation-based Park) and Taman Warisan Pertanian (Orchard-based Park) in Putrajaya. Insect sampling was done using yellow pan trap at 20 points for two weeks for each park. Vegetation structure of number of trees, number of shrubs, percentage canopy cover, percentage land cover and microclimate parameters of air temperature, relative humidty, solar radiation and wind speed were measured at each park. The findings showed that Taman Warisan Pertanian was significantly greater in insect abundance and richness implying that insect communities were more attracted due to the variety of fuiting trees (fruiting season), low in temperature and wind speed. However, Taman Rimba Alam showed significantly lower air temperature (up to 1.3°C) and solar radiation and higher relative humidity due to significantly greater canopy coverage compared to the other two parks. This study shows that types of park have influence on the vegetation structure, microclimate and insect communities. This study assists the urban forest managers and planners in the future planning in optimizing the ecosystem services of each park.